The effect of climate on human comfort using wind cooling standards - Gregorsk and Duhok province as a model (Journal of the College of Basic Education, 2022)
This study deals with the climate and the comfort of man and his various activities in the city of Dohuk, the goal is to know the climate in that region, and the extent of its impact on the comfort of man, as the rise and fall of any element of the climate in a place affects those other climatic elements and then affects the comfort of the individual and his activities.The research included the two climatic stations of Dohuk and Zakho for the period 1986-2020 and statistically analyzed it and the climatic elements (solar radiation - temperature - wind speed - air humidity - rain) in the presence of discrepancies between the two study stations, and this is due to the variation of geographical influences from inside and outside the studied area, which affects In the individual's comfort and activity, and to know this effect, the wind cooling and Gregorsk standards were used to determine the best seasons for human comfort.